HUBUNGAN STIGMA SOSIAL TERHADAP PERILAKU LOST TO FOLLOW-UP PADA PASIEN HIV/AIDS DENGAN TERAPI ARV - Mufidah, Dewi (STIKES Widyagama Husada, 2025)
Social stigma against HIV/AIDS patients is a significant issue that can affect adherence to antiretroviral therapy (ART). This stigma often leads to discrimination and social isolation, which can affect the health behavior of patients. The aim of this study is to determine the influence of social stigma on lost to follow-up behavior in HIV/AIDS patients receiving ARV therapy at RSUD Dr. Saiful Anwar. The research method used is cross-sectional with a descriptive analytic design. The research population consists of all HIV patients who undergo examinations at the Tropical Infectious Diseases polyclinic of RSUD Dr. Saiful Anwar, totaling 670 respondents. The sample taken consisted of 251 respondents using purposive sampling technique. Data were collected through questionnaires and analyzed using the Spearman's rho statistical test. The research results showed that most respondents had a high category of stigma amounting to 162 respondents (64.5%) and the majority of respondents exhibited a moderate Lost To Follow-Up behavior category with 137 respondents (54.6%) at Dr. Saiful Anwar Hospital, East Java Province. Statistical analysis yielded a p-value of 0.000, which indicates a significant relationship between social stigma and lost to follow-up behavior. The research results indicate that social stigma high can influence patient behavior in terms of engagement with treatment. These findings are very important, considering the challenges faced by HIV/AIDS patients in the context of existing stigma. Therefore, it is important for stakeholders in healthcare services to design interventions that can reduce social stigma and raise awareness about HIV/AIDS. Interventions that involve community education, psychosocial support, and family involvement can help create a more supportive environment for HIV/AIDS patients, making them feel more comfortable continuing their ARV therapy. Stigma sosial terhadap pasien HIV/AIDS merupakan masalah signifikan yang dapat mempengaruhi kepatuhan terhadap terapi antiretroviral (ARV). Stigma ini sering menyebabkan diskriminasi dan isolasi sosial, yang dapat mempengaruhi perilaku kesehatan pasien. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh stigma sosial terhadap perilaku lost to follow-up pada pasien HIV/AIDS yang menerima terapi ARV di RSUD Dr. Saiful Anwar. Metode penelitian yang digunakan adalah cross-sectional dengan desain deskriptif analitik. Populasi penelitian terdiri dari semua pasien HIV yang melakukan pemeriksaan di poli Tropik Infeksi RSUD Dr. Saiful Anwar, sebanyak 670 responden. Sampel yang diambil sebanyak 251 responden menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner dan dianalisis dengan uji statistik Spearman's rho. Hasil penelitian sebagian besar responden memiliki stigma kategori tinggi sebanyak 162 responden (64,5%) dan Sebagian besar responden memiliki Perilaku Lost To Follow-Up kategori cukup sebanyak 137 responden (54,6%) Di Rumah Sakit Dr Saiful Anwar Provinsi Jawa Timur. Analisis statistik menghasilkan nilai p sebesar 0,000, yang mengindikasikan adanya hubungan signifikan antara stigma sosial dan perilaku lost to follow-up. Hasil penelitian menunjukkan bahwa stigma sosial tinggi dapat mempengaruhi perilaku pasien dalam hal keterlibatan dengan pengobatan. Temuan ini sangat penting, mengingat tantangan yang dihadapi oleh pasien HIV/AIDS dalam konteks stigma yang ada. Oleh karena itu, penting bagi para pemangku kepentingan dalam layanan kesehatan untuk merancang intervensi yang dapat mengurangi stigma sosial dan meningkatkan kesadaran tentang HIV/AIDS. Intervensi yang melibatkan pendidikan masyarakat, dukungan psikososial, dan pelibatan keluarga dapat membantu menciptakan lingkungan yang lebih mendukung bagi pasien HIV/AIDS, sehingga mereka merasa lebih nyaman untuk melanjutkan terapi ARV mereka.